The Metaphor of Celebrity : Canadian Poetry and the Public, 1955-1980 - Deshaye, Joel, 1977- (Book collections on Project MUSE., 2013)
The Metaphor of Celebrity is an exploration of the significance of literary celebrity in Canadian poetry. It focuses on the lives and writing of four widely recognized authors who wrote about stardom -- Leonard Cohen, Michael Ondaatje, Irving Layton, and Gwendolyn MacEwen -- and the specific moments in Canadian history that affected the ways in which they were received by the broader public. Joel Deshaye elucidates the relationship between literary celebrity and metaphor in the identity crises of celebrities, who must try to balance their public and private selves in the face of considerable publicity. He also examines the ways in which celebrity in Canadian poetry developed in a unique way in light of the significant cultural events of the decades between 1950 and 1980, including the Massey Commission, the flourishing of Canadian publishing, and the considerable interest in poetry in the 1960s and 1970s, which was followed by a rapid fall from public grace, as poetry was overwhelmed by greater popular interest in Canadian novels."--Publisher website